Compositional heterogeneity in CsyFA1−yPb(BrxI1−x)3 perovskite films and its impact on phase behavior. Issue 12 (25th October 2021) - Barrier, Julien; Beal, Rachel E.; Gold-Parker, Aryeh; Vigil, Julian A.; Wolf, Eli; Waquier, Louis; Weadock, Nicholas J.; Zhang, Zihan; Schelhas, Laura T.; Nogueira, Ana Flavia; McGehee, Michael D.; Toney, Michael F.
Abstract : We study the phase behavior of hybrid organic–inorganic metal-halide perovskite and propose a simple method to assess heterogeneity in the <100 nm length scales. Abstract : Hybrid organic inorganic lead halide perovskite semiconductors of the form Cs y FA1− y Pb(Br x I1− x )3 are promising candidate materials for high-efficiency photovoltaics. Notably, cation and anion substitution can be used to tune the band gaps to optimize performance and improve stability. However, multi-component materials can be prone to compositional and structural inhomogeneity and the extent, length scale and impact of this heterogeneity on lead halide perovskite properties are not well understood. Here we use synchrotron X-ray diffraction to probe the evolution of crystal structure across the tetragonal-to-cubic phase transition for a series of Cs y FA1− y Pb(Br x I1− x )3 thin films with x = 0.05 to 0.3 and y = 0.17 to 0.40. We find that the transition occurs across a broad temperature range of approximately 40 °C, much larger than for pure compounds such as MAPbI3 and MAPbBr3 . We hypothesize that this smearing of the phase transition is due to compositional inhomogeneities that give rise to a distribution of local transition temperatures and we estimate the composition varies by about 10% to 15% with likely greater heterogeneity for the halide anion than the cation. This approach of mapping the transition is a simple and effective method of assessing heterogeneity, enabling evaluation of its impact.